2021
DOI: 10.31234/osf.io/3cq8n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analyzing GPS Data for Psychological Research: A Tutorial

Abstract: The ubiquity of location data-enabled devices provides novel avenues for psychology researchers to incorporate spatial analytics into their studies. Spatial analytics use GPS data to assess and understand mobility behavior (e.g., locations visited, movement patterns). This tutorial provides a practical guide to using GPS data in R, introducing researchers to key procedures and resources for conducting spatial analytics. We show readers how to clean GPS data, compute mobility features (e.g., time spent at home,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…GPS points were excluded if they were outside of sub-Saharan Africa (<1% of GPS coordinates per participant). Interpoint distances were totaled over each participant’s roughly 90-day observation period [ 12 ]. Mobility was summarized as the average distance traveled per week to account for certain days of the week with outliers of distance traveled (eg, staying home on Sundays) that can bias centrality estimates [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GPS points were excluded if they were outside of sub-Saharan Africa (<1% of GPS coordinates per participant). Interpoint distances were totaled over each participant’s roughly 90-day observation period [ 12 ]. Mobility was summarized as the average distance traveled per week to account for certain days of the week with outliers of distance traveled (eg, staying home on Sundays) that can bias centrality estimates [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mobility was summarized as the average distance traveled per week to account for certain days of the week with outliers of distance traveled (eg, staying home on Sundays) that can bias centrality estimates [ 13 ]. Two other measures were also described: the number of unique places visited (deduplicated points within 25 m of one another, based on smartphones’ 5-20-m GPS point accuracy [ 12 ]), and the percent of GPS points recorded away from home [ 7 ]. To calculate the latter measure, GPS points were dichotomized as being located within or outside a home buffer region.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, while a few recent studies found in MMC take a situational approach, only a minority of studies clearly distinguished between-person from within-person effects or leveraged mobile log data (Aalbers et al, 2021;Dogruel & Schnauber-Stockmann, 2020;Sewall et al, 2020). Likewise, recent calls for measuring person-specific effects (Beyens et al, 2020) and geospatial effects (Muller et al, 2022) are still largely absent within psychological research on mobile media. Given that intra-personal dynamics and situational factors are crucial for a holistic understanding of media effects, research cannot make full use of psychological perspectives without adopting such advancements.…”
Section: Integrating and Advancing Mobile Media Psychologymentioning
confidence: 99%
“…In particular, while a few recent studies found in MMC take a situational approach, only a minority of studies clearly distinguished between-person from within-person effects or leveraged mobile log data (Aalbers et al, 2021;Dogruel & Schnauber-Stockmann, 2020;Sewall et al, 2020). Likewise, recent calls for measuring person-specific effects (Beyens et al, 2020) and geospatial effects (Müller et al, 2022) are still largely absent within psychological research on mobile media. Given that intra-personal dynamics and situational factors are crucial for a holistic understanding of media effects, research cannot make full use of psychological perspectives without adopting such advancements.…”
Section: Integrating and Advancing Mobile Media Psychologymentioning
confidence: 99%